Separation of benzene from alkanes using 1-ethyl-3-methylpyridinium ethylsulfate ionic liquid at several temperatures and atmospheric pressure: Effect of the size of the aliphatic hydrocarbons - Emilio J. González (2010)
The ionic liquid 1-ethyl-3-methylpyridinium ethylsulfate, [EMpy][ESO4], was studied for the separationof benzene from aliphatic hydrocarbons (octane or nonane) by solvent extraction through the determinationof the (liquid + liquid) equilibrium (LLE) of the ternary systems: {octane (1) + benzene(2) + [EMpy][ESO4] (3)} and {nonane (1) + benzene (2) + [EMpy][ESO4] (3)} at T = (283.15 and 298.15) Kand atmospheric pressure. Binodal curves were determined using the cloud point method, and tie-linecompositions were obtained by density measurements. The values of selectivity and distribution coefficient,derived from the tie-line data, were used to decide if this ionic liquid can be used as potential solventfor the separation of benzene from aliphatic hydrocarbons using liquid extraction. These resultswere analyzed and compared to those previously reported for the systems {hexane + benzene+ [EMpy][ESO4]} and {heptane + benzene + [EMpy][ESO4]}. The experimental results show that thisionic liquid is suitable for the extraction of benzene from mixtures containing octane and nonane. Theconsistency of tie-line data was ascertained by applying the OthmerTobias and Hand equations. Theexperimental results for the ternary systems were well correlated with the NRTL model. No literaturedata were found for the mixtures discussed in this paper.